2020
DOI: 10.1155/2020/1347054
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Variability in Lean Manufacturing: A Fuzzy Value Stream Mapping Approach

Abstract: In this paper, value stream mapping (VSM) is integrated with fuzzy set theory to incorporate variability and uncertainty in the lean production system. VSM is one of the primary analytical tools for identifying waste and optimizing a production line. However, the standard VSM fails to consider the variability in manufacturing environments, which is, in fact, one of the root causes of waste. Therefore, this article proposes fuzzy VSM to overcome this weakness. Two alternative forms of fuzzy numbers, triangular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…A conveyor manufacturing company was selected as a case study due to the high variety and low volume process [19]. The manufacturing system is make-to-order type and has a high variety of products with varying process parameters [20,21]. Due to the high customized order from the customer a product family was selected based on their weight, component type, changeover time, shape and size.…”
Section: Methodsmentioning
confidence: 99%
“…A conveyor manufacturing company was selected as a case study due to the high variety and low volume process [19]. The manufacturing system is make-to-order type and has a high variety of products with varying process parameters [20,21]. Due to the high customized order from the customer a product family was selected based on their weight, component type, changeover time, shape and size.…”
Section: Methodsmentioning
confidence: 99%
“…4.3.2 Decision-making method. The uncertainty and inherent variability of data are the root causes of waste (Liu and Yang, 2020), so there are some decision-making methods that are used in VSM research to deal with these uncertainties, such as analytic hierarchy process, fuzzy and other multiple criteria decision-making methods (Singh et al, 2006a;Lu et al, 2011;Jordan et al, 2020;Luz et al, 2021). Through literature analysis, it can found that fuzzy theory was used to analyze data related to time, inventory and other operating variables in VSM (Braglia et al, 2009).…”
Section: Technology Expansion 431 Simulation Analysismentioning
confidence: 99%
“…Afterwards, these methods were used to map the value stream and to determine the best future-state VSM (Lu et al , 2011). Recently, some scholars have used triangular fuzzy numbers and normal fuzzy numbers to describe the time interval, inventory and other operating variables in VSM based on the multiattribute characteristics of data, and build a fusion model of fuzzy and VSM (Liu and Yang, 2020).…”
Section: Abstract and Research Topic Analysismentioning
confidence: 99%
“…Keykavoussi and Ebrahimi (2020) developed a new fuzzy approach of cost-time profile (CTP) that has been considered and compared to draw future VSM. Liu and Yang (2020) proposed a fuzzy VSM to consider the variability in manufacturing environments. They used two alternative forms of fuzzy number: triangular fuzzy numbers (TFNs) and normal fuzzy numbers (NFNs).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lean Thinking thus emerged as an effective way to continuously decrease costs and improve profits by utilizing the minimum required level of essential attributes such as time, space, machine, equipment, and energy to produce a product or provide a service. Liu and Yang (2020) claim that value stream mapping (VSM) is one of the primary analytical tools for identifying waste and optimizing a production line. The value of a product also increases when wastes from transportation, inventory, waiting, over-production, overprocessing, defects, and rework are eliminated or reduced (Sullivan, McDonald, and Aken, 2002).…”
Section: Introductionmentioning
confidence: 99%